Investigation Process of Criminal Action Fraud Acceptance of Civil Servants - Miftah Nur Asrofi; Siti Rodhiyah Dwi Istinah; Ira Alia Maerani; Sri Kusriyah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
The purpose of this study is to find out and analyze the process of investigating criminal acts of fraud in the recruitment of civil servants at the Pacitan Police Resort. To find out and analyze the factors causing the occurrence of criminal acts of fraud against the acceptance of Candidates for Civil Servants at the Pacitan Resort Police. This study used an empirical juridical approach, with descriptive analysis research specifications. The data used in this research was secondary data. The method of data collection is obtained from literature study, then analyzed qualitatively. The results of this study are the process of investigating the fraudulent recruitment of civil servants has been running according to the procedures for the police to summon witnesses, summon suspects and confiscate in accordance with the Investigation Order. The factors that cause the occurrence of the crime of fraud against the acceptance of prospective civil servants or the PNS recruitment system, legislation and law enforcement. External factors are in a forced condition, there is an opportunity to do evil, in a certain party pressure and it is the nature of a person.